On alpha-prime and Weakly alpha-prime Submodules - Thawatchai Khumprapussorn (My University, 2018)
We have introduced the notion of $\alpha$-prime and weakly $\alpha$-prime submodules as a generalization of prime submodules. Some basic properties of $\alpha$-prime and weakly $\alpha$-prime submodules are the extension of prime submodules. Finally, after introducing the notion of $\alpha$-prime submodules, we also define and study the concept of $\alpha$-prime ideals in a ring.
Keywords: Alpha (finance); Prime element; Associated prime; Intelligent Tutoring Systems and Adaptive Learning